Kepemimpinan Direktur Berpengaruh pada Peningkatan Kreatifitas Tenaga Pendidik - Fereddy Siagian; Listyaningsih Listyaningsih; Susilawati Susilawati (Alignment:Journal of Administration and Educational Management, 2021)
This study aims to determine whether the director's leadership has a positive effect on increasing the creativity of educators at the Cirebon Maritime Academy. The research method used in this research is quantitative methods to process the data obtained from the research location, which is data in the form of numbers or quantitative data that is raised. The sample used amounted to 266 respondents consisting of all employees who work within the AMC Cirebon and also students who are studying at AMC Cirebon taken with a non-probability sampling technique, namely the method of purposive sampling, because in determining the sample in this study certain criteria are considered. The analysis used in this research is validity test, reliability test, simple linear regression, hypothesis test with partial regression test (t test). Analysis using simple linear regression results Y = 17.057 + 0.463X can be seen that the regression equation shows an influence which is positive from the leadership variable to increase the creativity of educators. The results of the t test have a probability value of sig = 0.000 which is smaller than a probability value of 0.05 or a value of 0.05 0.000 (then Ho is rejected and Ha is accepted, meaning that the regression coefficient is significant. The conclusion is that the leadership of the director (X) has a significant effect on increasing creativity of educators (Y). Keywords: Director's Leadership, Improving the Creativity of Educators.